PERAN MODERASI ENVIRONMENTAL MANAGEMENT ACCOUNTING PADA GREEN INNOVATION DAN GREEN INTELLECTUAL CAPITAL TERHADAP FINANCIAL PERFORMANCE - Alifia Farah Shaffira (2023)
The purpose of this study is to examine how the influence of environmental management accounting (EMA) moderates the relationship between green innovation which consists of 2 components, namely green product innovation, green process innovation and green intellectual capital on financial performance. The population used in this research is the PROPER participating manufacturing sector companies listed on the Indonesia Stock Exchange in 2019-2022. The samples obtained in this study were carried out using a purposive sampling method by producing 154 sample companies. Hypothesis testing was carried out using multiple linear regression analysis which showed that the variables green process innovation, green intellectual capital and the interaction variables from EMA and green product innovation, green intellectual capital have a significant relationship to financial performance. Meanwhile, green product innovation and EMA moderation with green process innovation have no effect on financial performance.